UMPSA educational technology innovation attracts attention at Asean TVET Conference 2025 - Mohd Nizam, Abdul Rashid (UMPSA, 2025)
KUALA LUMPUR, 13 August 2025 – Three educational technology innovations from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) became the focus of visitors when exhibited at the ASEAN TVET Conference 2025 held at the World Trade Centre (WTC) here.